Clinical, immunological, molecular characteristics and outcomes of stem cell transplantation in ZAP70 deficiency: a single-center experience - AlQahtani, Fai; Al Shaqaq, Azhar; Al-Saud, Bandar; AlRumayyan, Nora; Mohammed, Reem; Arnaout, Rand; Elshorbagi, Sahar; Albuhairi, Sultan; Al-Ahmari, Ali; Ayas, Mouhab; Al-Saedi, Hawazen; Hawwari, Abbas; et al. (Frontiers in Immunology, 2025)
BackgroundZeta-chain-associated protein kinase 70 (ZAP70) deficiency is a rare autosomal recessive T+B+NK+ combined immunodeficiency characterized by heterogeneous clinical and immunologic phenotypes. Because of the limited number of reported cases, data guiding optimal management and hematopoietic stem cell transplantation (HSCT) strategies remain scarce.MethodsWe retrospectively reviewed all patients with genetically confirmed ZAP70 deficiency treated at King Faisal Specialist Hospital and Research Centre. Data on pre-HSCT clinical and immunologic features, transplant characteristics, post-HSCT complications, immune reconstitution, and long-term outcomes were recorded.ResultsThirteen patients with a median age at symptom onset of 1 month were identified. The most frequent initial presentations were recurrent respiratory infections and cutaneous manifestations. Autoimmune complications and lymphoproliferation were observed in several patients. Eleven of thirteen patients (84.6%) exhibited profound CD8+ T-cell lymphopenias and two had near-normal CD8+ T-cell counts with impaired T-cell function. Eleven patients underwent HSCT, including seven from Human Leukocyte Antigen (HLA)-matched family donors, two from one-antigen mismatched related donors, one from a haploidentical mother (matched for graft-versus-host disease risk but mismatched for rejection), and one from an unrelated cord blood donor. Two patients required a second transplant because of poor immune reconstitution. Of the 11 patients who underwent HSCT, 8 (73%) remain alive with a median follow-up of 7 years (range, 1–15), and most demonstrated resolution of clinical manifestations.ConclusionHSCT remains the only curative treatment for ZAP70 deficiency. Myeloablative conditioning regimens appear to promote more robust and durable immune reconstitution. In critically ill patients with severe infections or end-organ damage, reduced-intensity or unconditioned HSCT can be considered as a life-saving approach, although subsequent interventions might be necessary.